Effectiveness of STAD Cooperative Learning Model with LKS Help on Mathematical Learning Outcomes of Class VIII Students - Istiqfar Istiqfar; Irma Magfirah (USN Kolaka, 2018)
The learning outcomes of mathematics are one of the benchmarks of the high and low quality of a mathematics learning process. This study aims to find out how the effectiveness of STAD type cooperative learning model with the help of worksheets on mathematics learning outcomes of class VIII students at MTs. Muhammadiyah Palleko in Takalar in 2014/2015 academic year. This research is quasi-experimental or quasi?experimental research. The instrument used in this study is the essay type learning test with a sample of 35 people, and the sampling technique used is saturated samples. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive analysis obtained the average of the two groups, namely the experimental class before treatment (pre-test) of 59.16 and after the surgery of (posttest) 75.61, the average pre-test control class was 54.56, and the post test average is 58.25. Whereas based on the results of relative efficiency and inferential analysis it can be concluded that the STAD type of cooperative learning model with the help of LKS is effective in improving the mathematics learning outcomes of the eighth-grade students of MTs. Muhammadiyah Palleko District of Taylar.